Kedudukan Janda Murtad Dalam Pembagian Waris Atas Harta Pewaris (Suami) - Qisthina Armalia Hirzi; Ani Setiawati; Afdol (Perspektif Hukum, 2019)
The research entitled "Apostate Widow’s Position In Sharing Her Heir’s Property",withthe problem of an apostate wife, so that it is necessary to question the right of an apostate widow to the property of the heir (husband), related to the obligatory will. Research based on legislation and case studies can obtain a conclusion that obligatory wills are known in Islamic law given to people who are not heirs because there is no blood relationship with the testator or because he is an heir but for some reason it is not recognized as an expert inheritance. people who have close relations with the testator but are not heirs because there is no blood relationship with the heir, including the adopted child. Widows according to Islam Law Compilation Book are heirs, although not because of blood relations, but if the widow is an apostate, then she is not as an heir, therefore the widow gets a part of the heir's assets but in the form of a mandatory will.